Robust Face Recognition via Multi-channel Models and Feature Selection - Alrjebi, Mustafa M M (Curtin University, 2017)
This thesis proposes various novel approaches to improve the performance of face recognition via using multi channels for face image representation. Methods proposed in this thesis are designed to solve different face recognition problems including Opened Mouth, Occlusions, Illumination variations, and Pose variations. All proposed methods have achieved significant improvements over state of the art methods.